Chopinowskie Igrzysko, Historia Międzynarodowego Konkursu Pianistycznego im. Fryderyka Chopina 1927–2015 Ada Arendt, Marcin Bogucki, Paweł Majewski, Kornelia Sobczak - Michalski, Grzegorz (Studia Chopinowskie, 2023)
w